Molecular modeling elucidates the cellular mechanism of synaptotagmin-SNARE inhibition: a novel plausible route to anti-wrinkle activity of botox-like cosmetic active molecules - Pathomwat Wongrattanakamon (2018)
© 2017 Springer Science+Business Media, LLC Synaptotagmin 1 (Syt1) is the Ca 2+ sensor protein with an essential role in neurotransmitter release. Since the wrinkle formation is due to the excessive muscle fiber stimulation in the face, a helpful stratagem to diminish the wrinkle line intenseness is to weaken the innervating neuron activity through Syt1 inhibition which is one of the possible therapeutic strategies against wrinkles. Recently, experimental evidence showed that botox-like peptides, which are typically used as SNARE modulators, may inhibit Syt1. In this work, we applied molecular modeling to (1) characterize the structural framework and (2) define the atomistic information of the factors for the inhibition mechanism. The modeling identified the plausible binding cleft able to efficiently bind all botox-like peptides. The MD simulations revealed that all peptides induced significant Syt1 rigidity by binding in the cleft of the C2A–C2B interface. The consequence of this binding event is the suppression of the protein motion associated with conformational change of Syt1 from the closed form to the open form. On this basis, this finding may therefore be of subservience for the advancement of novel botox-like molecules for the therapeutic treatment of wrinkle, targeting and modulating the function of Syt1.